2007
DOI: 10.1370/afm.721
|View full text |Cite
|
Sign up to set email alerts
|

Improving Communication Between Doctors and Breast Cancer Patients

Abstract: PURPOSE We wanted to assess the effectiveness of intensive education for physicians compared with a traditional session on communicating with breast cancer patients.METHODS A randomized controlled trial was conducted in practices in London, Hamilton, and Toronto, Canada, with 17 family physicians, 16 surgeons, and 18 oncologists, and with 102 patients of the surgeons and oncologists. Doctors were randomized to 1 of 2 continuing education approaches: a traditional 2-hour version (control group), or a new 6-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 21 publications
(10 reference statements)
2
58
0
3
Order By: Relevance
“…These communication skills were applied in the follow-up of oncologic patients, in particular regarding the dialogue concerning possible therapy-related side effects and the importance of compliance and adherence to therapy (Mallinger et al, 2005;Stewart et al, 2007). Although endocrine therapy for postmenopausal breast cancer is generally well tolerated and the majority of adverse effects are mild to moderate, there are a certain number of patients who experience these as distressing (above all, hot flushes, musculoskeletal complaints/arthralgia and vaginal dryness).…”
Section: Discussionmentioning
confidence: 99%
“…These communication skills were applied in the follow-up of oncologic patients, in particular regarding the dialogue concerning possible therapy-related side effects and the importance of compliance and adherence to therapy (Mallinger et al, 2005;Stewart et al, 2007). Although endocrine therapy for postmenopausal breast cancer is generally well tolerated and the majority of adverse effects are mild to moderate, there are a certain number of patients who experience these as distressing (above all, hot flushes, musculoskeletal complaints/arthralgia and vaginal dryness).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that communication skills can be improved with effective training, and that effective communication improves medical outcomes, safety, patient adherence, patient satisfaction, and provider satisfaction and efficiency. [5][6][7][8][9][10][11][12][13][14] Organization-wide communication skills improvement programs are rare and reports are limited to case studies. 15 We designed and implemented an experiential, relationship-centered communication skills course and measured its impact on patient satisfaction, physician empathy, burnout, and self-efficacy in a large, multispecialty academic medical center.…”
Section: Introductionmentioning
confidence: 99%
“…This was entitled "Innovative Training to Improve Physician Communication with Breast Cancer Patients". [11] We wanted to answer this research question: Does intensive education improve physician communication with breast cancer patients? The research team was supported by a breast cancer patient advisory group.…”
Section: Studies Of Patient-centered Carementioning
confidence: 99%
“…Bu çal›flma "Hekimlerin Meme Kanseri Hastalar› ile ‹letiflimini Gelifltiren Yenilikçi bir E¤itim" olarak adland›r›lm›flt›. [11] Araflt›rma sorumuz flu flekildeydi: "Hekimlerin meme kanseri hastalar› ile iletiflimleri yo¤un bir e¤itim ile iyilefltirilebilir mi?" Araflt›rma ekibi, bir meme kanseri hastalar› dan›flma grubu taraf›ndan desteklendi.…”
Section: Bireyin Bir Bütün Olarak Kavranmas›unclassified